Psychological and organisational aspects of age management in organisations = Psychologiczne i organizacyjne aspekty zarządzania wiekiem w organizacjach - Witkowski, Stanisław; Bartosz, Bogna (Zielona Góra: Faculty of Economics and Management Press)
In article we present selected issues of age management in organizations. They pointed to the lack of rationale for the discriminatory policies of some companies to employees aged 50+. Attention of managers was paid to the problem of age management in organizations, conditioned by an increase in the number of employees 50+.
Keywords: zmiany demograficzne; pracownicy 50+; zarządzanie wiekiem; dobre praktyki; demographic changes; employees 50+; age management; good practices